Actual State and Changes of Flora and Vegetation in the Broczówka Steppe Reserve - Cwener, Anna; Nowak, Marcin (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
This paper presents floristic characterization of xerothermic plant associations and analysis of changes of flora within Broczówka steppe reserve. The floristic research was carried out in 2004-2009. Numerous species that were noted here almost 30 years ago were not found in the present study, the size of other populations decreased. Nevertheless, many plant species occurring in the reserve are rare, endangered or protected. Six major plant associations, impoverished form of two ones and one plant community are distinguished in the whole area of the reserve. Occurrence of two plant associations was not confirmed.